2020
DOI: 10.1126/sciadv.abb6595
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the activation of T cells with glycopolymer-modified dendritic cells by enhancing cell interactions

Abstract: Dendritic cell (DC) modification to enhance antigen presentation is a valuable strategy in cancer immune therapy. Other than focusing on regulating interactions between DC and antigens, we intend to promote cell interactions between DC and T cell by cell surface engineering. T cell activation is greatly improved and generates higher tumor toxicity with the aid of the synthetic glycopolymer modified on the DC surface, although the glycopolymer alone shows no effect. The great promotion of DC–T cell attraction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…pMAG or pMAM was then grafted on the cell membranes by glycopolymers-chloroalkane, as previously reported. 32,34 The cells were observed by fluorescence microscopy, and images of randomly chosen fields were captured.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…pMAG or pMAM was then grafted on the cell membranes by glycopolymers-chloroalkane, as previously reported. 32,34 The cells were observed by fluorescence microscopy, and images of randomly chosen fields were captured.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the control group, the expression of the intracellular nerve cell markers, β3-tubulin and the nestin gene, increased 76-fold and 7-fold, respectively (Figure 5B), and the purity of the neurofilaments increased significantly (Figure 5C). The MWNTs/PDMS delivery device can also be exploited for the development of new therapies such as dendritic cell (DC) vaccines, 31,32 which activate T-cells to promote the body's immune response, providing new possibilities for cancer treatment. 33 We showed that pDNA expressing HaloTag protein (pHTP) could be delivered into DC cells using the MWNTs/PDMS device; poly(N-methacryloylglucosamine) (pMAG) and poly(N-methacryloylmannosamine) (pMAM) could then be grafted to the cell membrane by glycopolymerschloroalkane (Figure 5D).…”
Section: Application Of the Lpt Surface In Cellmentioning
confidence: 99%
“…26 For another example, cell surface engineering of glycopolymers promoted the contacts between different cell types through carbohydrate–lectin binding. 215,216 In this way, glycopolymer-engineered cancer cells induced a strong stimulation to M1-type macrophages, and glycopolymer-engineered dendritic cells also activated T cells much more efficiently. 215,216 Accordingly, such a glycopolymer-based cell engineering strategy displayed great potential in cancer immunotherapy.…”
Section: Applications Of Cell-based Biocompositesmentioning
confidence: 98%
“…215,216 In this way, glycopolymer-engineered cancer cells induced a strong stimulation to M1-type macrophages, and glycopolymer-engineered dendritic cells also activated T cells much more efficiently. 215,216 Accordingly, such a glycopolymer-based cell engineering strategy displayed great potential in cancer immunotherapy. Moreover, the DNA coatings on different cells were used to control cell–cell interactions by virtue of the sequence-dependent DNA hybridization.…”
Section: Applications Of Cell-based Biocompositesmentioning
confidence: 98%
“…Dendritic cell (DC) modification for enhancement of antigen presentation has emerged as a highly successful strategy in tumor immune therapy. Previous studies demonstrated that synthetic glycopolymer modified on the DC surface through facilitating DC interaction with T cells markedly elevated T cell activation and results in higher tumor toxicity ( Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%